Faktor Yang Mempengaruhi Kesediaan Suami Sebagai Akseptor Vasektomi - Oni, Dechoni Rahmawati; Eka Ariningtyas, Ristiana (INVOLUSI: Jurnal Ilmu Kebidanan, 2025)
Background: The Family Planning Program (KB) is a program that Background: Family Planning (KB) is one of the important programs in an effort to control population growth and improve the welfare of families and communities. Among the available contraceptive methods, vasectomy has become a popular option for men who have decided to end their reproductive abilities. A vasectomy is a minor surgical procedure that stops the flow of sperm from the testicles to the male reproductive tract. Research Objectives: To analyze the knowledge factors, and attitudes that influence men's decisions to use vasectomy as a contraceptive method. The study also aims to provide better insights into how educational and informational efforts can improve vasectomy acceptance. Research Method: This study will use an analytical survey research design with a sample of 20 husbands. The data collected will be analyzed using statistical tests with a significance level of 5%. Research Results: The results of the study showed that the variables of knowledge and attitudes were related to the husband's willingness to be an acceptor of vasectomy birth control.Conclusion: Based on the results of the research that has been conducted, it shows that there is a relationship between knowledge and husband's attitude towards willingness as an acceptor of MOP which is shown by the p-value value in the knowledge variable 0.015 and in the attitude variable 0.004 where the p-value is smaller than the significance value with an error rate of 5%. Keywords: MOP, contraception, husband